2020
DOI: 10.1080/09658211.2020.1849308
|View full text |Cite
|
Sign up to set email alerts
|

Convicting with confidence? Why we should not over-rely on eyewitness confidence

Abstract: Eyewitness memory researchers have recently devoted considerable attention to eyewitness confidence. While there is strong consensus that courtroom confidence is problematic, we now recognise that an eyewitness's initial confidence in their first identificationin certain contextscan be of value. A few psychological scientists, however, have confidently, but erroneously claimed that in real-world cases, eyewitness initial confidence is the most important indicator of eyewitness accuracy, trumping all other fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Others have demonstrated that when memory performance is extremely low, the accuracy of high-confidence identifications decreases (Giacona et al, 2021). Others yet have pointed to failures to replicate the finding that high confidence implies high accuracy (Sauer et al, 2019) and have also called into question what we know about the accuracy of high-confidence identifications in real cases (Berkowitz et al, 2020). Our work augments these arguments by clarifying how data examining the confidence-accuracy relationship ought to be analyzed and by providing the field, broadly defined, with explicit criteria that can be used to evaluate the strength of claims pertaining to the confidence-accuracy relationship.…”
mentioning
confidence: 99%
“…Others have demonstrated that when memory performance is extremely low, the accuracy of high-confidence identifications decreases (Giacona et al, 2021). Others yet have pointed to failures to replicate the finding that high confidence implies high accuracy (Sauer et al, 2019) and have also called into question what we know about the accuracy of high-confidence identifications in real cases (Berkowitz et al, 2020). Our work augments these arguments by clarifying how data examining the confidence-accuracy relationship ought to be analyzed and by providing the field, broadly defined, with explicit criteria that can be used to evaluate the strength of claims pertaining to the confidence-accuracy relationship.…”
mentioning
confidence: 99%
“…Although the confidence-accuracy relationship has been somewhat inconsistent across previous alibi generation studies (Cardenas et al, 2020;Leins and Charman, 2016), confidence ratings in the current study were not related strongly to the accuracy of the alibi. Thus, our findings suggest that legal personnel should be careful not to overstate the informativeness of an alibi provider's confidence, echoing similar concerns from the eyewitness context (Berkowitz et al, 2020). Ultimately, accused persons may not only produce a false alibi owing to schema usage, but may also be fully confident that the alibi is accuratefurther damaging their credibility.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, the confidence expressed in eyewitness testimonies can have a large impact on the outcome of a trial (Tenney et al, 2008). Perhaps due to the enormous stakes of such testimonies, there is a lively debate on how trustworthy confidence ratings of eye witnesses really are (Berkowitz et al, 2020;Juslin et al, 1996;Loftus & Greenspan, 2017;Wixted & Wells, 2017). As these examples demonstrate, understanding how much we can trust the confidence expressed by others has important implications for many domains as disparate as law, medicine, and education.…”
Section: Introductionmentioning
confidence: 99%